Two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst as well as preparation method and application thereof

By constructing a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst, the problems of high treatment cost of dodecylmorpholine contamination liquid and low efficiency of photocatalyst in the prior art are solved, and the effect of efficient degradation of dodecylmorpholine is achieved, reducing the effect of reducing the Energy consumption and secondary pollution are avoided.

CN119114121AActive Publication Date: 2024-12-13HUAQIAO UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411228710.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The prior art has high cost when treating dodecylmorpholine contaminated liquid, is wasteful of energy and secondary pollution, and there are few photocatalysts used to degrade dodecylmorpholine, making it challenging to prepare high-efficiency photocatalysts.

Method used

Using a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst, the band gap width and visible light absorption range of Bi2WO6 are regulated, the surface area and reactive sites are increased, the photogenerated electron life is extended, the photocatalytic performance is improved, and the dodecane is degraded. morpholine.

Benefits of technology

It has achieved efficient degradation of dodecylmorpholine, significantly improved the degradation rate, simple preparation of catalytic materials, low energy consumption, easy recycling, avoid secondary pollution, and improve light utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114121A_ABST
    Figure CN119114121A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst as well as a preparation method and application of the two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst. According to the preparation method, an Al atomic layer in MAX-phase Ta4AlC3 is etched through an etching method, then a single-layer MXene material Ta4C3 is prepared through ultrasonic and other mechanical stripping means, and finally nano-microspheres Bi2WO6 are generated on the surface of Ta4C3 in situ through a hydrothermal method, so that the two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst is obtained. According to the two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst disclosed by the invention, the electron transfer capability of Bi2WO6 is enhanced, the visible light absorption wavelength range of Bi2WO6 is widened, the electron-hole recombination rate is reduced, and the photocatalytic performance is improved. Under the condition of illumination for 60 min, the degradation efficiency of the two-dimensional layered Ta4C3 loaded Bi2WO6 composite catalyst for degrading dodecyl morpholine reaches 65% and is 2.3 times that of a Bi2WO6 monomer, effective degradation of dodecyl morpholine in a water body is achieved, no other energy is consumed, and the method is simple, safe, environmentally friendly and suitable for industrial production. The method has important significance on low-energy-consumption and pollution-free treatment of the flotation agent dodecyl morpholine in the salt lake brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of salt lake brine treatment and environmental protection, and specifically relates to a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst and a preparation method and application thereof. Background Art

[0002] Potash fertilizer is widely used in agriculture, providing strong support for increasing agricultural production. Currently, more than 70% of the world's potash fertilizer is produced by using foam flotation. Morpholine flotation agents have become the primary flotation agents for potash extraction because of their relatively small usage in the process of potash extraction.

[0003] When using froth flotation to extract potassium, dodecylmorpholine and octadecylamine are added. The flotation effect is best when the carbon chain length of morpholine is between 12 and 18. As the carbon chain length of the flotation agent increases, it is difficult to be naturally degraded. Allowing dodecylmorpholine to flow into the water body will inevitably have a serious impact on the water environment. Therefore, finding a green and efficient method for treating flotation agents is an important part of the subsequent treatment of potash fertilizer production.

[0004] At present, many factories use electrocatalysis to treat dodecylmorpholine contaminated liquid. However, the current electrocatalysis treatment method also has shortcomings. During the electrocatalysis process, it is necessary to continuously increase the current outside the contaminated liquid, which increases the cost of pollutant treatment and wastes a lot of energy. In addition, new pollutants will be introduced during the electrocatalysis process to cause secondary pollution. Therefore, it is necessary to explore a green and environmentally friendly method for treating dodecylmorpholine contaminated liquid.

[0005] Photocatalysis is a green technology that can convert available light energy into chemical energy. It has the advantages of no secondary pollution, simple operation, mild reaction conditions, etc. It is widely used in degradation, hydrogen production, nitrogen fixation, etc. The photocatalytic mechanism is that when the semiconductor material is irradiated by sunlight, the singletons in the valence band will jump to the conduction band to form electron-hole pairs. The holes in the valence band have strong oxidizing ability because of the loss of electrons, and the conduction band has strong reducing ability because of the electron transition. Particles with excellent redox properties (·OH, O2ˉ, H2O2) will be generated in the valence band and the conduction band to undergo redox reactions with pollutants to degrade pollutants in water.

[0006] Although a large number of catalysts have been used in environmental pollution treatment, there are few photocatalysts used to degrade dodecylmorpholine. Therefore, the use of photocatalytic technology to degrade dodecylmorpholine is challenging, the most important of which is to prepare an efficient photocatalyst. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst and a preparation method and application thereof to improve the above-mentioned problems.

[0008] Specifically, Bi2WO6 is an n-type semiconductor that has attracted research attention due to its excellent visible light absorption performance. Its band gap value E g =2.6-2.9eV, low toxicity, easy preparation, deep valence band formed by hybridization of Bi6s and O2p orbitals, and excellent chemical stability. However, the main disadvantages of pure semiconductors including Bi2WO6 are photocorrosion, rapid recombination of photogenerated carriers, poor adsorption, low reusability, and low utilization of sunlight. In order to overcome these problems, various strategies have been adopted, such as doping metals and non-metals and constructing heterojunctions.

[0009] MXene is a new type of 2D material of transition metal carbide or nitride, which can usually be prepared by selectively etching the atomic layer from its parent MAX phase by a mixture of HF or strong acid (HCl) and fluoride salts (NaF, LiF and NH4F). Because its material surface has a large number of hydrophilic functional groups (-OH, -O and -F), these functional groups can form a strong connection between MXene materials and many semiconductors; in addition, MXene materials have good metallic conductivity and can enhance carrier migration. Therefore, MXene materials have great potential as co-catalysts in the field of photocatalysis. The present invention uses a heterojunction between Bi2WO6 and Ta4C3 to improve the photocatalytic performance of Bi2WO6. Bi2WO6 is compounded with the two-dimensional layered MXene material Ta4C3 to increase the bandgap width E g The visible light absorption wavelength range of Bi2WO6 is reduced, which broadens the visible light absorption wavelength range of Bi2WO6 and effectively improves the light utilization rate of Bi2WO6. The specific surface area of ​​Bi2WO6 is increased during the reaction process, thereby increasing the surface reaction active sites of Bi2WO6. The electrons on the valence band of Bi2WO6 can be transferred to Ta4C3, which reduces the recombination of photogenerated electrons and holes, increases the lifetime of photogenerated electrons, thereby improving the photocatalytic performance, and further improving the degradation rate of dodecylmorpholine.

[0010] Based on the above ideas, the technical solution adopted by the present invention to solve its technical problems is:

[0011] A method for preparing a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst, comprising:

[0012] (1) Etching Al from MAX phase Ta4AlC3 to obtain multilayer Ta4C3;

[0013] (2) washing the multilayer Ta4C3 prepared in step (1) with deionized water, and after intercalation with tetramethylammonium hydroxide, washing the resulting solution with anhydrous ethanol until the upper clear liquid is no longer yellowish, and then washing once with deionized water to obtain washed multilayer Ta4C3;

[0014] (3) The multilayer Ta4C3 obtained by washing in step (2) is subjected to ice-water bath ultrasound under inert gas protection, and is centrifuged to obtain layered Ta4C3;

[0015] (4) Dissolve Bi(NO3)3·5H2O in ethylene glycol, add the layered Ta4C3 obtained in step (3) to obtain solution A;

[0016] (5) dissolving Na2WO4·2H2O in deionized water and adding polyvinylpyrrolidone to obtain solution B;

[0017] (6) adding solution B in step (5) dropwise to solution A, and adjusting the pH value to 1.5 to 3.5 to obtain solution C;

[0018] (7) After the solution C obtained in step (6) is stirred evenly, it is hydrothermally reacted at 150-165° C. for 16-24 h, cooled to room temperature, taken out, centrifuged, washed and vacuum dried to obtain a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst.

[0019] In a preferred embodiment of the present invention, in step (1), the particle size of the MAX phase Ta4AlC3 used is 300-400 mesh; the etching uses an HF solution with a concentration of 40-45%, the volume of the HF solution is 30-50 ml, the etching temperature is 45-55°C, the stirring speed is 400-600 rpm / min, and the etching time is 24-72h.

[0020] In a preferred embodiment of the present invention, in step (2), the number of washing times with deionized water is 6 to 8 times, and the pH of the MXene suspension after washing is 5 to 6; 20 ml of 5 to 25% tetramethylammonium hydroxide is used for intercalation, and the intercalation time is 18 to 24 hours.

[0021] In a preferred embodiment of the present invention, in step (3), an inert gas is introduced during the ultrasonic mechanical stripping process, and the ultrasonic temperature is controlled below 20°C, and the ultrasonic time is 90 min to 120 min; the centrifugal conditions are 6500 to 8500 rpm / min, and the centrifugal time is 25 to 40 min.

[0022] In a preferred embodiment of the present invention, the inert gas is nitrogen.

[0023] In a preferred embodiment of the present invention, in step (5), the mass ratio of Bi2WO6 to layered Ta4C3 is in the range of 90% to 99%.

[0024] In a preferred embodiment of the present invention, in step (7), the stirring rate is 150 rpm / min to 250 rpm / min, and the stirring time is 25 min to 35 min; the washing method is alternating washing with water and ethanol, the vacuum drying temperature is 45 to 70°C, and the vacuum drying time is 18 to 24 h.

[0025] The present invention also provides a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst prepared according to the above preparation method.

[0026] The present invention also provides an application of the above-mentioned two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in degrading dodecylmorpholine in water.

[0027] In a preferred embodiment of the present invention, the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst is added to a water body containing dodecylmorpholine; wherein the ratio of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst to the water body containing dodecylmorpholine is 0.09-0.13 g: 95-120 mL, the concentration of dodecylmorpholine in the water body is 7.5-9.5 mmol / L, and the pH value of the water body is 2.0-3.5;

[0028] The water body to which the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst is added is placed in a dark place and stirred for 30 to 60 minutes, and then reacted under light conditions for 60 to 90 minutes.

[0029] Among them, by placing the water body with the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in the dark and stirring it for 25 to 35 minutes, the catalyst and the solution can reach adsorption equilibrium.

[0030] In a preferred embodiment of the present invention, a 300W xenon lamp plus a filter is used to simulate sunlight to provide the light source.

[0031] It should be noted that the equipment, reagents, processes, parameters, etc. involved in the present invention are conventional equipment, reagents, processes, parameters, etc. unless otherwise specified, and are not described as embodiments.

[0032] All ranges recited herein include all point values ​​within the range.

[0033] In the present invention, the "room temperature" refers to the normal ambient temperature, which can be 10-30°C.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention prepares a 2D layered MXene material Ta4C3, regulates the morphology of Bi2WO6 and constructs a heterojunction with Ta4C3 to synthesize a two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst. It produces efficient redox groups in water to degrade dodecyl morpholine.

[0036] 2. The catalytic material of the present invention is simple to prepare, easy to operate, and has low energy consumption. Compared with the existing DMP degradation catalyst, the catalytic effect is good, and the catalyst is easy to recover. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the X-ray diffraction pattern of MAX phase Ta4AlC3, multilayer Ta4C3 and single layer Ta4C3 in Example 1 of the present invention.

[0038] Figure 2 This is the X-ray diffraction pattern of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 1 of the present invention, wherein the X-ray diffraction pattern located at the top is the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst, and the X-ray diffraction pattern located at the bottom is Bi2WO6.

[0039] Figure 3 These are scanning electron microscope photos of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 1 of the present invention, wherein a) is MAX phase Ta4AlC3, b) is multilayer Ta4C3, c) is single layer Ta4C3, d) is pure phase Bi2WO6, and e and f) are Ta4C3 / Bi2WO6 composites.

[0040] Figure 4 This is a performance curve diagram of the photocatalytic degradation of dodecylmorpholine solution by the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 1 of the present invention.

[0041] Figure 5 This is a performance curve diagram of the photocatalytic degradation of dodecylmorpholine solution by the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 2 of the present invention.

[0042] Figure 6 This is the cyclic degradation spectrum of the photocatalytic degradation of dodecylmorpholine solution by the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 2 of the present invention.

[0043] Figure 7 This is the calculated band gap spectrum of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 2 of the present invention.

[0044] Figure 8This is the steady-state fluorescence spectrum of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst in Example 2 of the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in more detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0046] Example 1

[0047] This embodiment provides a method for preparing a two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst and a process for photocatalytic degradation of 7-9 mmol / L dodecylmorpholine. Specifically:

[0048] (1) MAX phase Ta4AlC3 was prepared by etching Al with 40 mL 40% HF at a constant temperature of 50°C to obtain multilayer Ta4C3;

[0049] (2) washing the multilayer Ta4C3 prepared in step (1) with deionized water 7 times until the pH value is greater than 5;

[0050] (3) The washed multilayer Ta4C3 in step (2) was subjected to intercalation reaction in 20 mL 5% tetramethylammonium hydroxide for 24 h;

[0051] (4) washing the solution obtained after the intercalation in step (3) with anhydrous ethanol until the supernatant is no longer yellow, and then washing once with deionized water;

[0052] (5) The multilayer Ta4C3 obtained in step (4) was subjected to ultrasonic treatment in an ice-water bath for 120 min under N2 protection;

[0053] (6) The multilayer Ta4C3 sample prepared in step (5) was centrifuged at 6800 rpm / min for 30 min to obtain a single-layer Ta4C3 dispersion, which was then freeze-dried for 24 h to obtain a single-layer Ta4C3 MXene material;

[0054] (7) 0.9701 g Bi(NO3)3·5H2O was dissolved in 40 mL ethylene glycol, and the layered Ta4C3 prepared in step (6) was added so that the mass ratio of Bi2WO6 to layered Ta4C3 was 25:1. The solution was ultrasonicated for 15 min and stirred at 150 rpm / min for 120 min to obtain solution A.

[0055] (8) 0.3297 g of Na2WO4·2H2O was dissolved in 20 mL of deionized water and 0.3 g of polyvinylpyrrolidone was added, and the mixture was stirred at 150 rpm / min for 120 min to obtain solution B;

[0056] (9) adding solution B in step (8) dropwise to solution A and adjusting the pH value to 3 with glacial acetic acid to obtain solution C, and stirring for 30 min;

[0057] (10) Pour solution C in step (9) into 100 mL Teflon liner and perform hydrothermal reaction at 160° C. for 16 h. After cooling to room temperature, take out, wash three times with deionized water and anhydrous ethanol by centrifugation, and then vacuum dry at 60° C. for 24 h to obtain a two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst;

[0058] (11) The prepared two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst was added to an aqueous solution of dodecylmorpholine at a concentration of 8 mmol / L for photocatalytic degradation. During the degradation, the reaction was first performed in the dark for 30 min, and then illuminated for 60 min under a 300 W Xe lamp simulating sunlight. Samples were taken every 10 minutes to test the degradation efficiency.

[0059] The X-ray diffraction pattern of the above-mentioned layered Ta4C3 is as follows Figure 1 As shown in the figure, the characteristic diffraction peak is the Ta4C3 peak. Compared with the MAX phase Ta4AlC3, the Al peak in the X-ray diffraction spectrum of the multilayer Ta4C3 disappears and only the (002), (013), and (016) crystal planes are retained, indicating that the Al atomic layer in the MAX has been successfully etched. Compared with the multilayer Ta4C3, the 2θ angle of the (002) crystal plane of the single-layer Ta4C3 becomes smaller. It can be seen from the Bragg equation that the diffraction angle becomes smaller and the interplanar spacing increases, which further indicates that the multilayer Ta4C3 is successfully stripped into a single-layer Ta4C3.

[0060] The X-ray diffraction spectrum of the two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst prepared above is as follows: Figure 2 As shown in the figure, the prepared Bi2WO6 has no impurity peaks and sharp characteristic peaks compared with the standard card, indicating that the prepared Bi2WO6 has a high purity. Due to the composite of Bi2WO6 and Ta4C3, the diffraction peak intensity of the pure phase Bi2WO6 powder has decreased, indicating that Bi2WO6 and Ta4C3 have been successfully composited, and further indicating that the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst has been successfully prepared. The scanning electron microscope image is shown in the figure. Figure 3 As shown, Figure 3 middle, Figure 3 a) is MAX phase Ta4AlC3, the blocky MAX phase matrix is ​​micron-level, Figure 3 b) is the MXene Ta4C3 with an accordion shape after etching away the Al atomic layer. Figure 3 c) is the layered Ta4C3 after ultrasonic exfoliation, Figure 3 d) is the prepared Bi2WO6. Figure 3e) and Figure 3 f) is a Ta4C3 / Bi2WO6 composite, composed of Figure 3 It can be seen that Bi2WO6 grows on the surface of Ta4C3.

[0061] The photocatalytic degradation of dodecylmorpholine was tested on the two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst, and the degradation effect was measured by UV spectrophotometer. Figure 4 As shown, single Bi2WO6 showed a certain effect of degrading dodecylmorpholine, but the degradation effect was slow and the degradation efficiency was low. After the introduction of Ta4C3, the degradation effect and degradation rate were significantly improved, and the degradation effect reached 38% within 60 minutes, indicating that the layered Ta4C3 / microspherical Bi2WO6 composite has a significant photocatalytic degradation effect on dodecylmorpholine.

[0062] Example 2

[0063] In this embodiment, the mass ratio of Bi2WO6 to Ta4C3 is changed to 100:3 based on the preparation method of Example 1. The two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst synthesized by the preparation method of Example 1 is taken, 0.1g is dispersed in 100mL 8mmol / L dodecylmorpholine aqueous solution and reacted in the dark for 30min to reach adsorption-desorption equilibrium. The degradation efficiency calculated by the photoreaction for 60min under 300W Xe lamp simulated sunlight is 64%. Compared with the monomer, it is significantly improved. In this embodiment, the catalyst is also tested for stability and repeated tests.

[0064] like Figure 6 As shown, from Figure 6 It can be seen that after five cycles of degradation, the efficiency is still above 50%, indicating that the photocatalytic performance of the material is good.

[0065] like Figure 7 As shown, Figure 7 This is the calculated band gap spectrum of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst. The calculation shows that the band gap of the monomer Bi2WO6 is 3.20eV, while the band gap of the composite catalyst is 3.17eV, indicating that the light response range of Bi2WO6 has not changed after being composited with Ta4C3.

[0066] Next, the prepared complexes were subjected to steady-state fluorescence tests, e.g. Figure 8 As shown, from Figure 8 It can be seen that the fluorescence intensity of the composite catalyst is lower than that of the pure phase, indicating that the recombination rate of electrons and holes in the composite catalyst is reduced, thereby improving the photocatalytic performance.

[0067] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing a two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst, characterized in that: include: (1) Etching Al from MAX phase Ta4AlC3 to prepare multilayer Ta4C3; (2) washing the multilayer Ta4C3 prepared in step (1) with deionized water, and after intercalation with tetramethylammonium hydroxide, washing the resulting solution with anhydrous ethanol until the upper clear liquid is no longer yellowish, and then washing once with deionized water to obtain washed multilayer Ta4C3; (3) The multilayer Ta4C3 obtained by washing in step (2) is subjected to ice-water bath ultrasound under inert gas protection, and is centrifuged to obtain layered Ta4C3; (4) Dissolve Bi(NO3)3·5H2O in ethylene glycol, add the layered Ta4C3 obtained in step (3) to obtain solution A; (5) dissolving Na2WO4·2H2O in deionized water and adding polyvinylpyrrolidone to obtain solution B; (6) adding solution B in step (5) dropwise to solution A, and adjusting the pH value to 1.5 to 3.5 to obtain solution C; (7) After the solution C obtained in step (6) is stirred evenly, it is subjected to hydrothermal reaction at 150-165° C. for 16-24 h, cooled to room temperature, taken out, centrifuged, washed and vacuum dried to obtain a two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the MAX phase Ta4AlC3 used is 300-400 mesh; the etching uses a 40-45% HF solution, the volume of the HF solution is 30-50 ml, the etching temperature is 45-55°C, the stirring speed is 400-600 rpm / min, and the etching time is 24-72h.

3. The preparation method according to claim 1, characterized in that: In step (2), the deionized water is used for washing 6 to 8 times, and the pH of the MXene suspension after washing is 5 to 6; 20 ml of 5 to 25% tetramethylammonium hydroxide is used for intercalation, and the intercalation time is 18 to 24 hours.

4. The preparation method according to claim 1, characterized in that: In step (3), an inert gas is introduced during the ultrasonic mechanical stripping process, and the ultrasonic temperature is controlled below 20° C. The ultrasonic time is 90 min to 120 min; the centrifugal condition is 6500 to 8500 rpm / min, and the centrifugal time is 25 to 40 min; the inert gas is nitrogen.

5. The preparation method according to claim 1, characterized in that: In the step (5), the mass ratio of Bi2WO6 to layered Ta4C3 is in the range of 90% to 99%.

6. The preparation method according to claim 1, characterized in that: In the step (7), the stirring rate is 150 rpm / min to 250 rpm / min, and the stirring time is 25 min to 35 min; the washing method is alternating washing with water and ethanol, the vacuum drying temperature is 45 to 70° C., and the vacuum drying time is 18 to 24 h.

7. A two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst prepared according to the preparation method according to any one of claims 1 to 7.

8. Use of the two-dimensional layered Ta4C3-supported Bi2WO6 composite catalyst according to claim 7 in degrading dodecylmorpholine in water.

9. The use according to claim 8, characterized in that: include: Adding the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst to a water body containing dodecylmorpholine; wherein the ratio of the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst to the water body containing dodecylmorpholine is 0.09-0.13 g: 95-120 mL, the concentration of dodecylmorpholine in the water body is 7.5-9.5 mmol / L, and the pH value of the water body is 2.0-3.5; The water body after adding the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst is placed in a dark place and stirred for 30 to 60 minutes to allow the two-dimensional layered Ta4C3-loaded Bi2WO6 composite catalyst and the water body to reach adsorption equilibrium; The adsorption equilibrium solution was reacted under light conditions for 60 to 90 minutes.

10. The use according to claim 9, characterized in that: A 300W xenon lamp plus a filter is used to simulate sunlight to provide lighting conditions.

Citation Information

Patent Citations

  • Rod-like WO3 / flaky g-C3N4 photocatalyst, preparation method and method for degrading dodecyl morpholine in salt lake brine

    CN116603557A

  • Black phosphorus / bismuth tungstate two-dimensional S-type heterojunction and preparation method and application thereof

    CN116832840A

  • NH2-MIL-88B (Fe) / Bi2WO6 composite photocatalyst as well as preparation method and application thereof

    CN117427692A

  • Synthesis strategy of supported transition metal carbides fenton-like catalysts and application thereof

    US20210283592A1